2013
DOI: 10.1002/acr.21949
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and Factors Related to Fatigue in Rheumatoid Arthritis: A Systematic Review

Abstract: Objective. Although patients with rheumatoid arthritis (RA) experience fatigue, little is known about its causes and consequences, and a fully developed theoretical model explaining the experience of fatigue in RA is lacking. Our goal was to systematically review studies in RA that examined factors related to fatigue to gain more insight into its possible causes and consequences. Methods. Medline, Web of Science, Scopus, and PsycINFO were searched for relevant studies. All studies with RA samples about the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
223
3
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(259 citation statements)
references
References 46 publications
15
223
3
13
Order By: Relevance
“…Being physically inactive may also increase fatigue. These findings are in line with a recent systematic review documenting that pain and physical function, in addition to depression, were the variables most strongly related to fatigue in RA patients (5). Previous studies have shown divergent results regarding the relationships between fatigue and disease activity measures (6,9).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Being physically inactive may also increase fatigue. These findings are in line with a recent systematic review documenting that pain and physical function, in addition to depression, were the variables most strongly related to fatigue in RA patients (5). Previous studies have shown divergent results regarding the relationships between fatigue and disease activity measures (6,9).…”
supporting
confidence: 90%
“…In our study, lower ESR at baseline was a statistically significant predictor of a higher fatigue level at 6 months. This negative relationship between ESR and fatigue has also been found in previous studies, but results are divergent and this needs further investigation (5,10,11).…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Minor or daily stressors (for example, negative interpersonal events) are associated with more fatigue and pain, elevated immune activity, and disease exacerbations [2, 11,15,23,27,34,35]. However, less clear are the results regarding major stressors, such as the death of a loved one.…”
Section: Prospective Studiesmentioning
confidence: 99%
“…Good quality social support has shown to protect against psychological distress and increase in physical symptoms [2,8,23]. It has, however, also been shown that problematic, unwanted, or stressful relationships lead to increased distress, higher symptom levels, and increased inflammatory activity in rheumatic diseases, thus indicating that the quality of social support is particularly important [2, 11,23,34]. Regarding the social aspects within the healthcare context, a satisfactory relationship between the care provider and patient, which, for example, consists of mutual trust and active participation of the patient in treatment and decision making, has been shown to be an important predictor of high patient engagement and well-being in inflammatory rheumatic diseases.…”
Section: Prospective Studiesmentioning
confidence: 99%